Engineering Ethics in Islam: An Evaluative and Comparative Study Between Cod of Ethics of Institution of Engineers, Bangladesh (IEB)and Code of Professional Conduct of Board of Engineers Malaysia (BEM) - Amanullah, Muhammad (IIUM Press, 2011)
During the past two centuries or so a number of buildings and bridges had been structurally failed and collapsed all over the world. Some of these incidents caused a sizeable number of human casualties. For instance, collapse of Tay Bridge in 1879 killed at least sixty persons. Beside the problems related to their design and construction, probably the failure to follow engineering ethics properly was partially responsible for these incidents. Growing engineering professionalism during the nineteenth century gave rise to the development of a number of famous engineering societies, such as American Institute of Electrical Engineers (AIEE ( (1884), American Institute of Mining Engineers (AIME) (1871), etc. On the other hand, responding to series of significant structural failures mentioned above, some engineering societies developed formal codes of ethics. Following these societies, engineers of Bangladesh (previous East Pakistan) established Institution of Engineers, Bangladesh (IEB). Likewise, Malaysian engineers established Board of Engineers Malaysia (BEM). Both of these societies have their codes of ethics. Islam also has offered a number of ethics to be followed by the engineers. Analyzing the related verses of the Qur’an and ahadith of the Prophet (pbuh), this paper intends to highlight these Islamic ethics and in light of them, tries to evaluate the codes of ethics of these two societies and compare between them. The paper may conclude that although the codes of ethics of IEB and BEM are supported by Islamic ethics they require further modification.